Meta-analysis on the efficacy and safety of Guanxin Shutong capsule in the treatment of angina pectoris of coronary heart disease - Wang, Yaqin; Zhang, Muchen; Zhang, Yan; Yin, Wenhao; Zhao, Shujun; Mao, Wenjun; Wang, Xuewei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to summarize all single clinical studies of Guanxin Shutong (GXST) capsule combined with Western medicine in the treatment of coronary heart disease angina pectoris and to systematically evaluate its efficacy and safety.MethodsThis study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Chinese and English databases were searched to collect the randomized controlled trials (RCTs) of GXST capsule combined with conventional Western medicine in the treatment of patients with angina pectoris of coronary heart disease and to extract the data. Cochrane Risk of Bias Tool was used to evaluate literature quality, and RevMan5.3 software was used to evaluate the outcome indicators, such as total effective rate of angina pectoris, frequency of angina pectoris, duration of angina pectoris, total effective rate of electrocardiogram (ECG), lipid level, inflammatory factor level, hemorheology, cardiac function, and adverse reactions, and to assess publication bias.ResultsA total of 27 RCTs with 3440 cases were identified. The results showed that the combined use of GXST capsule was more effective in terms of total effective rate of angina pectoris, frequency of angina pectoris, duration of angina pectoris, and total effective rate of ECG. In addition, the combined use of GXST capsule had more advantages in reducing total cholesterol, low-density lipoprotein cholesterol, interleukin-6, tumor necrosis factor–α, high-sensitivity C-reactive protein, and whole-blood viscosity and increasing left ventricular ejection fraction and high-density lipoprotein cholesterol. However, for triglyceride and interleukin-1, there were two different results before and after the sensitivity analysis, which were attributed to the quality of the included literature. In terms of plasma viscosity and adverse reactions, after excluding the literature with large heterogeneity, sensitivity analysis indicated that the combined use of GXST capsule was helpful to reduce plasma viscosity and adverse reactions.ConclusionsGXST capsule combined with conventional Western medicine has better efficacy and safety in the treatment of angina pectoris of coronary heart disease compared with Western medicine alone. However, our study still has some limitations. Thus, more standardized RCTs are needed in future studies to verify the conclusions, and longer follow-up periods need to be designed to explore the long-term efficacy.